IMPROVING THE WATER ALLOCATION MANAGEMENT MECHANISM BASED ON A DIGITAL MONITORING SYSTEM AND DIGITAL PLATFORM (International Congress on Economics, Management and Business Studies, 2026)
This thesis studies the issues of improving water distribution based on the use of digital monitoring systems and digital platforms in water resources management. The study analyzes the possibilities of real-time monitoring and management of water consumption using modern information technologies, including sensors, GIS systems and online platforms. It was found that the introduction of digital technologies serves to reduce water losses, make the distribution process transparent and ensure efficient use of resources. As a result, scientific and practical proposals were developed to optimize the water distribution process and increase economic efficiency in the agricultural sector.
Keywords: digital monitoring, water distribution, digital platform, water resources, GIS, sensor systems, smart water management, real-time monitoring, irrigation, resource efficiency.